2010
DOI: 10.18433/j31g6c
|View full text |Cite
|
Sign up to set email alerts
|

ASK1-P38 Pathway is Important for Anoikis Induced by Microtubule-Targeting Aryl Chloroethylureas

Abstract: PURPOSE. We investigated the involvement of MAPK signaling in the cell death mechanisms of classical microtubule interfering agents (MIA) and aryl-3-(2-chloroethyl)ureas (CEU) acting as antimitotics, along with CEU that don’t affect directly microtubules (non-MIA CEU). METHODS. To ascertain the activated signaling pathway profile of MIA and non-MIA CEU, Western blot, immunoprecipitation and transfection experiments were performed. RESULTS. Non-MIA CEU do not activate p38, as opposed to MIA, and the exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
(69 reference statements)
1
3
0
Order By: Relevance
“…Phosphorylation and dephosphorylation of Ser83 have both been correlated with ASK1 activation (Kim et al, 2001;Gu et al, 2009;Fortin et al, 2010;Yang et al, 2010). However, recent work have emphasized the role of Ser83 phosphorylation of ASK1 in induction of apoptosis (Fortin et al, 2010;Yang et al, 2010), and this is in agreement with our observations of IQ-induced ASK1 phosphorylation at Ser83 and subsequent apoptosis. Because p38/JNK could also be activated by other upstream kinases in addition to ASK1, further experiments are needed to determine whether ASK1 plays a critical role in apoptotic signaling.…”
Section: Discussionsupporting
confidence: 92%
“…Phosphorylation and dephosphorylation of Ser83 have both been correlated with ASK1 activation (Kim et al, 2001;Gu et al, 2009;Fortin et al, 2010;Yang et al, 2010). However, recent work have emphasized the role of Ser83 phosphorylation of ASK1 in induction of apoptosis (Fortin et al, 2010;Yang et al, 2010), and this is in agreement with our observations of IQ-induced ASK1 phosphorylation at Ser83 and subsequent apoptosis. Because p38/JNK could also be activated by other upstream kinases in addition to ASK1, further experiments are needed to determine whether ASK1 plays a critical role in apoptotic signaling.…”
Section: Discussionsupporting
confidence: 92%
“…[22. 23-26] Since we showed that MTBT-induced G 2 /M arrest depends on functional p38, it is possible that mitotic arrest induced by other drugs is also p38 dependent. Thus, we tested if p38 is required for the cell cycle arrest induced by microtubule disruption under our experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The MAPK member, p38, is a serine/threonine protein kinase, which responds to several cellular processes and external stress signaling, such as cell differentiation, cell proliferation, inflammation regulation and cell death (14,15). ASK1 is the most well-studied family member and is an upstream kinase of the JNK and p38 pathways (16,17). It has been demonstrated that ASK1 is activated in response to a variety of stress-related stimuli via distinct mechanisms and activates MKK4 and MKK3, which in turn activate JNK and p38 (18).…”
Section: Introductionmentioning
confidence: 99%